Multi‐analyte profile analysis of plasma immune proteins: altered expression of peripheral immune factors is associated with neuropsychiatric symptom severity in adults with and without chronic hepatitis C virus infection. Issue 2 (29th December 2013) - Huckans, Marilyn; Fuller, Bret E.; Olavarria, Hannah; Sasaki, Anna W.; Chang, Michael; Flora, Kenneth D.; Kolessar, Michael; Kriz, Daniel; Anderson, Jeanne R.; Vandenbark, Arthur A.; Loftis, Jennifer M.
Abstract Background The purpose of this study was to characterize hepatitis C virus (HCV)‐associated differences in the expression of 47 inflammatory factors and to evaluate the potential role of peripheral immune activation in HCV‐associated neuropsychiatric symptoms—depression, anxiety, fatigue, and pain. An additional objective was to evaluate the role of immune factor dysregulation in the expression of specific neuropsychiatric symptoms to identify biomarkers that may be relevant to the treatment of these neuropsychiatric symptoms in adults with or without HCV. Methods Blood samples and neuropsychiatric symptom severity scales were collected from HCV‐infected adults (HCV+, n = 39) and demographically similar noninfected controls (HCV−, n = 40). Multi‐analyte profile analysis was used to evaluate plasma biomarkers. Results Compared with HCV− controls, HCV+ adults reported significantly (P < 0.050) greater depression, anxiety, fatigue, and pain, and they were more likely to present with an increased inflammatory profile as indicated by significantly higher plasma levels of 40% (19/47) of the factors assessed (21%, after correcting for multiple comparisons). Within the HCV+ group, but not within the HCV− group, an increased inflammatory profile (indicated by the number of immune factors > the LDC) significantly correlated with depression, anxiety, and pain. Within the total sample, neuropsychiatric symptom severity was significantly predicted by protein signatures consisting of 4–10 plasma immune factors; protein signatures significantly accounted for 19–40% of the variance in depression, anxiety, fatigue, and pain. Conclusions Overall, the results demonstrate that altered expression of a network of plasma immune factors contributes to neuropsychiatric symptom severity. These findings offer new biomarkers to potentially facilitate pharmacotherapeutic development and to increase our understanding of the molecular pathways associated with neuropsychiatric symptoms in adults with or without HCV.